Implementation of Transportation, Warehouse and Distribution to Supply Chain Management: Study Literature Review - Andri Primadi; Saribanon, Euis; Yuliantini, Yuliantini; Nashrullah, Nashrullah; Tohir, Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Abstract: The article on the implementation of transportation, warehouse and distribution on supply chain management is an article within the scope of operational management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research within the scope of operational management. The research method used is descriptive qualitative. The data collection technique uses literature studies/literature reviews. Data were obtained from previous studies that are relevant to this study and sourced from academic online media such as Publish or Perish, Google Scholar, Jurnal Sinta, DOAJ and Garuda. The results of this study are as follows: 1) Transportation affects supply chain management; 2) Warehouses affect supply chain management; and 3) Distribution affects supply chain management. Keyword: Supply Chain Management, Transportation, Warehouse, Distribution